(untitled) (Journal of Madenat Alelem, 2010)
Fifty two Chromate resistant bacterial strains were isolated from industrial sewage contaminated with Chromate, different soil sample, polluted river sediment, and many hospitals sewage. The isolates showed resistance to concentrations of Chromate, which was available as K2Cr2O7 or H2CrO3. Forty two isolates were gram negative bacilli and the other gram positive bacilli. In addition to resistance of Chromate as a heavy metal, they were able to resist some antibiotics. The results showed that most isolates were antibiotic multi-resistant. Growth curve of selected isolates showed an obvious decline at high concentrations of Chromate.